The Effect of Economic Literature and Social Environment on Impulsive Buying Behavior Through Online Shop in Karanggeneng Village Community - Saputra, Riedwan Adhie; Harsono, H (Proceedings International Conference on Education Innovation and Social Science, 2022)
This research is quantitative research. This study aims to describe the influence of economic literacy and social environment on impulsive buying behavior through online shop media in Karanggeneng village community. The sample used in this study was the Karanggeneng village community, totaling 152 samples. Samples were taken through random sampling method. The data collection method used a questionnaire that was applied in the google form. The result of this research is that economic literacy has no significant and positive effect on impulsive buying behavior, because the value of tcount -2.141 < ttable 1.655. While the social environment has a positive and significant effect on impulsive buying behavior, because the value of tcount is 3,221 > ttable 1,655. And the combination of economic literacy and social environment has a significant and positive influence on impulsive buying behavior, because the calculated f value is 8.918 > f table is 3.06.